Does Corporate Governance Matter? - Yunia, Dabella; Mutmainah, Siti (KnE Social Sciences, 2024)
This study examines the influence of corporate governance on performance. Corporate governance is measured using the corporate governance index developed by Schweizer et al. (2019). Research data were obtained from the documentation of the Indonesia Stock Exchange (www.idx.co.id). The data were tested using multiple linear regression analysis. The results of the regression analysis document showed significant evidence of the influence between corporate governance index, board age, ownership concentration, and performance. The findings of this research contribute to corporate management in improving and maintaining corporate governance. Furthermore, this research can also be used by regulators as a consideration in designing and implementing guidelines for corporate governance mechanisms. The results of this research can also be used by investors as a consideration in investing in companies with good corporate governance. Keywords: board age, corporate governance, ownership concentration, performance